Field-Based Human Factors in Home and Community Settings: Challenges and Strategies. (September 2015) - Holden, Richard J.; Valdez, Rupa S.; Hundt, Ann Schoofs; Marquard, Jenna; Montague, Enid; Nathan-Roberts, Dan; Or, Calvin; Zayas-Cabán, Teresa
Studies of complex health and healthcare phenomena such as transitions of care, chronic disease management, or care coordination, often require field work spanning people, time, and place. The scope of such field work often includes patients and their families and settings such as the home and community. Human factors researchers are identifying the challenges associated with conducting such work and are developing practical strategies. This panel gathers human factors experts to address the question: What are the challenges to and strategies for conducting human factors field research on health and healthcare with multiple individuals including patients, over longer periods of time, and across settings including the (patient) home and community? Panelists answer this question by describing their personal experiences with multiple studies and provide vignettes for grounding an interactive panelist-audience discussion.